1993
DOI: 10.1038/eye.1993.175
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ocular motility problems following scleral buckling surgery

Abstract: Nottingham SUMMARYThe incidence and severity of extraocular muscle imbal ance after conventional scleral buckling surgery was determined for 70 eyes of 68 patients with primary rheg matogenous retinal detachment. Fifty-eight eyes had cir cumferential silicone explants, 10 eyes had radial sponges and 2 had both. Sixty-five per cent of eyes showed some restriction of ocular motility and 72 % of patients had diplopia within their field of binocular single vision (BSV). The more extraocular muscles the explant was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…6,8,9 Regression analysis of our patients has not, however, shown an association between these variables and magnitude of strabismus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…6,8,9 Regression analysis of our patients has not, however, shown an association between these variables and magnitude of strabismus.…”
Section: Discussionmentioning
confidence: 95%
“…3 The strabismus is reported greater with multiple VR procedures, encircling buckling elements rather than sectoral explants, and increasing number of muscles the explant is in direct contact with. 2,[5][6][7][8] The strabismus has been attributed to several mechanisms including globe distortion, fibrotic adhesions, mass effect on muscle pulleys, the effects of local anaesthetic (LA), and sensory disturbance. Macula off RD and reduced postoperative visual acuity (VA) are associated with poorer outcomes for binocular vision.…”
Section: Introductionmentioning
confidence: 99%
“…8 Spencer concluded that ocular muscle imbalance was related to the position of explant, and the more muscles the explant was placed under, the more directions of gaze were likely to be restricted. 1 They also showed that restriction was more likely to occur in the direction away from the buckle, suggesting tethering of the muscles, but can also occur towards the explant.…”
Section: Mechanical Factorsmentioning
confidence: 95%
“…8 Spencer studied 68 patients following scleral buckling surgery and 72% developed symptomatic diplopia. 1 Waddell reported on 79 patients following scleral explant surgery and showed that only 24% had no diplopia or motility restriction. Thirty-three percent had symptomatic restrictions.…”
Section: Incidencementioning
confidence: 97%
See 1 more Smart Citation